2009
DOI: 10.1017/s136898000999053x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Mediterranean and non-Mediterranean foods during the last four decades: comparison of several geographical areas

Abstract: The present study suggests that European countries, especially those in the Mediterranean area, have experienced a 'westernisation' process of food habits, and have increasingly similar patterns of food availability (mainly non-Mediterranean food groups) among them. Measures must be taken to counteract these tendencies and to avoid their possible negative consequences. It is also crucial to find ways to promote and preserve the Mediterranean diet and its lifestyle in modern societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 44 publications
3
61
0
3
Order By: Relevance
“…Deviations from healthy dietary patterns can be an adverse effect of nutrition transition. According to WHO recommendations, the Mediterranean diet represents a healthy dietary pattern (24) and several studies have demonstrated the protective effect of the Mediterranean diet against chronic diseases (42)(43)(44)(45) . Therefore, nutritional education on the importance of a healthy diet at the population level and developing policies to facilitate the availability of healthy foods could reduce the rapid trend of obesity and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deviations from healthy dietary patterns can be an adverse effect of nutrition transition. According to WHO recommendations, the Mediterranean diet represents a healthy dietary pattern (24) and several studies have demonstrated the protective effect of the Mediterranean diet against chronic diseases (42)(43)(44)(45) . Therefore, nutritional education on the importance of a healthy diet at the population level and developing policies to facilitate the availability of healthy foods could reduce the rapid trend of obesity and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Food availability is derived from production, supply, different usages and wastages of food and indicates apparent consumption instead of real consumption (19,23) . Assessing the trend in availability of food components is a useful tool for evaluation of changes in dietary patterns and can applied to defining dietary patterns (24)(25)(26) . For the calculation of food availability in a country, the amount of food exported, used for animals and in agriculture or wasted is subtracted from the amount of food produced and imported; the annual amount of available energy from food items is then divided by the total population of a country in the same period.…”
Section: Databasementioning
confidence: 99%
“…However, this is not the case, as the availability of the Non-Mediterranean foods has increased to a much greater extent compared to Mediterranean foods (27,28,30) . The upward trend of MAI in Northern Europe was the result of increased availability of Mediterranean food products such as fruits and vegetables (12,30) . The study shows that the MAI values in Mediterranean Europe were higher than the MAI values presented by Northern and Central Europe.…”
Section: Discussionmentioning
confidence: 99%
“…3 These changes have been fairly rapid, causing imbalance between people, genetic programming, environmental exposures and, consequently, occurrence of disease.…”
mentioning
confidence: 99%
“…3,[16][17][18] Based on the Food and Agriculture Organization food balance sheets, these studies concluded that a majority of countries have tended to drift away from a Mediterranean-like dietary pattern, with the Mediterranean European countries, including Portugal, experiencing the greatest decrease in Mediterranean diet adherence. 3,16,17 Among these studies, Mediterranean Adequacy Index was used by da Silva et al 17 , and found that the greatest changes occurred in Mediterranean Europe, recording high availability of non-Mediterranean food groups (animal fats, vegetable oils, sugar and meat), whereas the availability of vegetables decreased. This is line with the aforementioned low cost production of these non-Mediterranean food groups compared with limited market supply of fruits and vegetables in European Union.…”
mentioning
confidence: 99%